Imminent eclampsia: the clinical state and the treatment with Avertin of 100 cases - Craig, Cecil (Division of Family Medicine, 2020)
The term eclampsia is derived from the Greek eklampien meaning a flesh, and its etymology suggests the acute onset of the convulsions. On the surface, therefore, it would appear paradoxical to define any state as being one of "imminent eclampsia". However, although the aetiology is unknown, sufficient knowledge of the preceding history and manifestations of eclampsia has accumulated to justify such a specific term. In a subsequent chapter, these symptoms and signs will be assessed and discussed in detail. Where the net of antenatal care is widespread and where such services are accepted and utilized by all who are pregnant in a community, the incidence of severe toxania and eclampsia is minimal. Few obstetricians in highly developed, civilized areas are afforded the opportunities for studing and treating any large numbers of cases of imminent eclampaia